The Effect of Promotion Costs, Financing Amount, and Third-Party Funds on Market Share at Pt Bank Syariah Indonesia - Adinda Afifa; Maidalena Maidalena; Juliana Nasution (Universitas Trunojoyo Madura, 2026)
This study aims to analyze the effect of promotional costs, financing amounts, and third-party funds (DPK) on the market share of PT Bank Syariah Indonesia Tbk (BSI). The study uses a quantitative approach with multiple linear regression methods. The data used are secondary data in the form of BSI's quarterly and annual financial reports obtained from official publications of Bank Syariah Indonesia and the Financial Services Authority (OJK). Data processing and analysis were carried out using IBM SPSS version 25 through classical assumption tests, regression tests, and partial and simultaneous hypothesis tests. The results show that promotional costs have a negative and significant effect on market share, indicating that the increase in the promotional budget has not been followed by optimal marketing strategy effectiveness. The amount of financing has a positive and significant effect on market share, so that financing is the main factor in expanding BSI's market share. Meanwhile, third-party funds (DPK) have a negative and insignificant effect on market share, indicating that the increase in DPK plays a more important role in maintaining liquidity than market expansion. Simultaneously, all three variables have a significant effect on market share with a coefficient of determination of 39.8%. These findings provide important implications for BSI management in formulating promotional strategies and financing optimization to strengthen the market position of Islamic banking.